Detection of Acaricidal Resistance in Rhipicephalus microplus from Mehsana District, Gujarat, India - Kalpeshkumar Patel, Mit; Rahimbhai Parsani, Husen; Kunhi Purayil, Shyma; Das, Bhupamani (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A study was conducted in Mehsana district, Gujarat, to assess acaricide resistance in Rhipicephalus (Boophilus) microplus, the most  common tick species infesting cattle and buffaloes in India. Tick samples were collected from both organized and unorganized farms  where treatment failures had been reported. The lethal concentration (LC50 and LC95) of fenvalerate and flumethrin was determined by  Adult Immersion Test (AIT). Results showed varying resistance levels to fenvalerate, including level I (RF > 5), level II (5.1 < RF < 25), and  level IV (RF > 41), while all isolates remained susceptible to flumethrin. Enzymatic assays revealed α- and β-esterase activity ranging from  4.05 ± 0.005 to 17.56 ± 0.182 and 2.34 ± 0.056 to 10.95 ± 0.54 μmol/min/mg protein, respectively. High resistance levels, particularly in  Navavas village, correlated with elevated esterase activity, suggesting metabolic resistance. However, some areas showed high enzyme  activity despite low resistance, possibly due to exposure to other synthetic pyrethroids. The findings highlight the urgent need for  alternative tick control strategies to combat emerging resistance in the region.
Keywords: Acaricide; Cattle; Resistance; Rhipicephalus microplus